Clusters as a probe of the equation-of-state of strongly interacting matter - Gläßel Susanne; Voronyuk Vadim; Winn Michael; Kireyeu Viktar; Coci Gabriele; Aichelin Jörg; Blume Christoph; Bratkovskaya Elena (EPJ Web of Conferences)
We investigate the influence of the equation-of-state (EoS) of strongly interacting matter created in heavy-ion collisions on the light cluster and hypernuclei production within the Parton-Hadron-Quantum-Molecular Dynamics (PHQMD) microscopic transport approach. In earlier PHQMD calculations, nucleon interactions were modeled using a static, density-dependent potential corresponding to the soft and hard equation-of-state. In this study, we incorporate a momentum-dependent potential for the baryon-baryon interaction, derived from the soft EoS. We study the influence of momentum dependent potential on light cluster production.